Covert human intelligence sources: the 'unlovely' face of police work - Billingsley, Roger (Waterside Press, 2009)
The contents of Covert Human Intelligence Sources (CHIS) cover such key matters as: What is meant by CHIS The legal framework The Regulation of Investigatory Powers Act 2000 (RIPA) Inherent powers and the position at Common Law 'Informers' and 'informants' Working methods and oversight Handlers, controllers and authorising officers Dangers and risks Human rights, proportionality and 'necessity' Corruption and 'noble cause corruption' Protection and the duty of care Undercover officers: strains, duties and requirements 'Official' participation in crime: how far is it legal? Motives of informers Records and management of information Juvenile informers Texts, public interest immunity and anonymity Debriefing and human memory The context of informer relationships 'Ownership' of intelligence and communications A European perspective General background, views and opinions.